Analysis of the differences in the management of a conventional and a takaful insurance company - Fonseca, Melbourne (2008)
The dissertation is based on the comaprison of takaful insurance company and a conventional insurance company in Bahrain. The dissertation takes a closer look at the performance of the insurance industry in Bahrain and the growth and development of the takaful insurance companies in the G.C.C region.